Role of the Hyaluronan receptor CD44 during porcine oocyte maturation - Yokoo, Masaki (Society for Reproduction and Development, 2007)
Previous of our study have been shown that CD44, the principal receptor of hyaluronan, is present in cumulus cell during oocyte maturation.Although hyaluronan-CD44 interaction has been implicated in cumulus expansion and/or oocyte maturation, the full significance of CD44 remain unknown.the objective of the present study was to further investigate the role of CD44 in cumulus expansion and oocyte maturation in pig. We demonstrated here in that CD44 has a key role in oocyte maturation but not in cumulus expansion.